Pre calc

Someone please help me prove these

A) cos^4x-sin^4x=cos2x




B)tanx=sin^2x/1+cos^2x


Please and Thank you

  1. 0
  2. 0
  3. 20
asked by Samantha
  1. looks like you need to review your basic identities and double-angle formulas:


    cos^4x-sin^4x
    = (cos^2x-sin^2x)(cos^2x+sin^2x)
    = cos^2x-sin^2x
    = cos2x

    (B) is clearly not true, since sin^2x/(1+cos^2x) has no asymptotes

    1. 0
    2. 0
    posted by Steve

Respond to this Question

First Name

Your Response

Similar Questions

  1. calc

    Where do I start to prove this identity: sinx/cosx= 1-cos2x/sin2x please help!! Hint: Fractions are evil. Get rid of them. Well, cos2x = cos2x - sin2x, so 1-coscx = 1 - cos2x - sin2x = 1 - cos2x + sin2x You should be able to

    asked by maria on October 21, 2006
  2. TRIG!

    Posted by hayden on Monday, February 23, 2009 at 4:05pm. sin^6 x + cos^6 x=1 - (3/4)sin^2 2x work on one side only! Responses Trig please help! - Reiny, Monday, February 23, 2009 at 4:27pm LS looks like the sum of cubes sin^6 x +

    asked by hayden on February 24, 2009
  3. Mathematics - Trigonometric Identities

    Let y represent theta Prove: 1 + 1/tan^2y = 1/sin^2y My Answer: LS: = 1 + 1/tan^2y = (sin^2y + cos^2y) + 1 /(sin^2y/cos^2y) = (sin^2y + cos^2y) + 1 x (cos^2y/sin^2y) = (sin^2y + cos^2y) + (sin^2y + cos^2y) (cos^2y/sin^2y) =

    asked by Anonymous on November 8, 2007
  4. tigonometry

    expres the following as sums and differences of sines or cosines cos8t * sin2t sin(a+b) = sin(a)cos(b) + cos(a)sin(b) replacing by by -b and using that cos(-b)= cos(b) sin(-b)= -sin(b) gives: sin(a-b) = sin(a)cos(b) - cos(a)sin(b)

    asked by Pablo on November 26, 2006
  5. Pre-Calc

    How do I solve this? My work has led me to a dead end. tan(45-x) + cot(45-x) =4 my work: (tan45 - tanx)/(1+ tan45tanx) + (cot45 - cotx)/(1 + cot45cotx) = 4 (1-tanx)/(1+tanx) + (1-cotx)/(1+cotx) = 4 Then I found a common

    asked by Jess on February 7, 2007
  6. algebra

    Can someone please help me do this problem? That would be great! Simplify the expression: sin theta + cos theta * cot theta I'll use A for theta. Cot A = sin A / cos A Therefore: sin A + (cos A * sin A / cos A) = sin A + sin A = 2

    asked by Valerie on February 18, 2007
  7. trig

    it says to verify the following identity, working only on one side: cotx+tanx=cscx*secx Work the left side. cot x + tan x = cos x/sin x + sin x/cos x = (cos^2 x +sin^2x)/(sin x cos x) = 1/(sin x cos x) = 1/sin x * 1/cos x You're

    asked by Devon on May 8, 2007
  8. trig

    Reduce the following to the sine or cosine of one angle: (i) sin145*cos75 - cos145*sin75 (ii) cos35*cos15 - sin35*sin15 Use the formulae: sin(a+b)= sin(a) cos(b) + cos(a)sin(b) and cos(a+b)= cos(a)cos(b) - sin(a)sin)(b) (1)The

    asked by Paul C on November 26, 2006
  9. math

    Prove that for all real values of a, b, t (theta): (a * cos t + b * sin t)^2

    asked by mathstudent on December 20, 2006
  10. Pre calc

    Someone please help me prove these A) cos^4x-sin^4x=cos2x B)tanx=sin^2x/1+cos^2x Please and Thank you

    asked by Bethany on April 14, 2017

More Similar Questions